2018
DOI: 10.1002/tesq.455
|View full text |Cite
|
Sign up to set email alerts
|

Speaking Anxiety and Strategy Use for Learning English as a Foreign Language in Full and Partial English‐Medium Instruction Contexts

Abstract: In recent years, Taiwan and other East Asian countries have begun to promote English‐medium instruction (EMI) at the tertiary level. Communicating through English in EMI classrooms is a basic requirement for English as a foreign language (EFL) learners, but it can be a challenge. Speaking a foreign language is a complex process that involves linguistic competence, speaking skills, and strategy use. Speaking strategies have been viewed as first aid devices used for interaction and communication, to address prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(123 citation statements)
references
References 47 publications
3
93
4
1
Order By: Relevance
“…According to Crookall and Oxford (1991) instructors can improve the classroom atmosphere using pair work, small group work and other organized activities. Chou (2018) recommends having online chatting among students as an activity to reduce anxiety that results from face-to-face communication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Crookall and Oxford (1991) instructors can improve the classroom atmosphere using pair work, small group work and other organized activities. Chou (2018) recommends having online chatting among students as an activity to reduce anxiety that results from face-to-face communication.…”
Section: Discussionmentioning
confidence: 99%
“…(2) giving additional guidance to students (3) utilizing more pair and group work in class; and (4) role-playing with preliminary activities to establish class rapport. Chou (2018) found that students especially in the full EMI context adopted practice or rehearsal strategies such as imitating native speakers of English, seeking out opportunities to speak, initiating conversations as often as possible and intentionally discussing unfamiliar topics. Zhiping and Paramasivam (2013) noted that instructors should make jokes, tell stories in class, show positive gestures to students' responses, appreciate students' answers and not call students' names in class.…”
Section: Coping With Speaking Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, since the beginning of the communicative era, speaking's development has gained the attention of both teachers and learners. Yet, it is a complex process including linguistic competence, oral skills, and strategy use (Chou, 2018).…”
Section: Introducing the Problemmentioning
confidence: 99%
“…The comunication competency will be considered by EFL students in this age since interpersonal communication skill lead the students to communicate with others by using English accurately, and by presenting the topic properly. Being able to speak English is the most demanding skill encountered by EFL students since English speaking is the most difficult skill of the four language skills that must be achieved by EFL students to involve in effectice communication [2][3][4]. There are three factors affecting the communication skill of EFL students, such as; langauge barriers, pshychological factors, learning enviroment, and language practice [5].…”
Section: Introductionmentioning
confidence: 99%